Descriptive Study of Healthy Lifestyle Community Movement During Covid-19 Pandemic Period of Diponegoro University Students Live in Jakarta - Rahmah, Syifa Rifqa Ainur; Fitria, Laila; Darundiati, Yusniar Hanani; Dewanti, Nikie Astorina Yunita (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
COVID-19 is a global pandemic phenomenon. Collage students are included in the second-largest age range contracting COVID-19 (24.7%) after the productive age range, namely 31-45 (30.4%) in 31 August 2020. This disease must be overcome by carrying out preventive activities, such as the practice of the Healthy Living Community Movement. This study aims to describe the practice of Healthy Living Community Movement of Diponegoro University students who live in Jakarta during the COVID-19 pandemic. This type of research is descriptive with a cross-sectional design. The sample in this study were Diponegoro students who lived in Jakarta with accidental sampling. The data analysis used was univariate. The results of this study found a good overview of Healthy Living Community Movement among students (72.2%). However, in practice, physical activity at least 30 minutes a day are still rarely done (53.7%). The majority of respondents have a fairly good knowledge (47.2%). However, the knowledge of the severity of smokers exposed to COVID-19 is still less likely to become intensive care patients (6.5%). Respondent's attitude was classified as positive (97.2%). The level of access to information about COVID-19 and the Healthy Living Community Movement of respondents was in a good category (68.5 %%). In addition, respondents are also motivated to do Healthy Living Community Movement by their social environments such as parents (83.3%) and friends (66.7%). It can be concluded that in addition to knowledge, the respondents' level of Healthy Living Community Movement practice is classified as good because it has covered all of these practices during the COVID-19 pandemic.